Ballistic Testing of an Aerogel/Starch Composite Designed for Use in Wearable Protective Equipment - John LaRocco; Taeyoon Eom; Tanush Duggisani; Ian Zalcberg; Jinyi Xue; Ekansh Seth; Nicolas Zapata; Dheeraj Anksapuram; Nathaniel Muzumdar; Eric Zachariah (Technologies)
Concussion is a costly healthcare issue affecting sports, industry, and the defense sector. The financial impacts, however, extend beyond acute medical expenses, affecting an individual’s physical and cognitive abilities, as well as increasing the burden on coworkers, family members, and caregivers. More effective personal protective equipment may greatly reduce the risk of concussion and injury. Notably, aerogels are light, but traditionally fragile, non-Newtonian fluids, such as shear-thickening fluids, which generate more resistance when compressive force is applied. Herein, a composite material was developed by baking a shear-thickening fluid (i.e., starch) and combining it with a commercially available aerogel foam, thus maintaining a low cost. The samples were tested through the use of a ballistic pendulum system, using a spring-powered launcher and a gas-powered cannon, followed by ballistic penetration testing, using two electromagnetic accelerators and two different projectiles. During the cannon tests without a hardhat, the baked composite only registered 31 ± 2% of the deflection height observed for the pristine aerogel. The baked composite successfully protected the hygroelectric devices from coilgun projectiles, whereas the projectiles punctured the pristine aerogel. Leveraging the low-cost design of this new composite, personal protective equipment can be improved for various sporting, industrial, and defense applications.